Importance of elbow flexor muscle strength and endurance in sport climbing - Michailov, M.; Lambreva, S.; Deneva, D.; Andonov, H. (Journal of Applied Sports Sciences, 2017)
The muscles that exert most during sport climbing are the finger flexors followed by elbow flexors (EF). Nevertheless, climbers` EF strength and endurance have not been tested in an isolated manner and EF endurance has not been assessed at differ-ent relative intensities. Purpose: To determine the importance of EF maximal strength and endurance in sports climbing. Methods:Nine male sports climbers and a control group of seven male sports students performed an EF maximal strength (MS) test and four EF endurance tests representing isometric muscle contractions at 90%, 70%, 50% and 30% of the maximal voluntary contraction (MVC). Results: Sports climbers sustained longer than the controls at 70 % (39±11 versus 28±7 s; p=0.044, ) and 50%MVC (57±10 versus 48±6 s; p=0.050 ). The highest effect size was estimated for the force-time integral related to body mass at 70% MVC (107±27 ver-sus 75±18 N.s/kg; p=0.018). The two groups did not differ in MS (313±52 versus 338±55 N; p=0.372) or MS related to body mass (4.6±0.6 versus 4.2±0.8 N/kg; p=0.623). Climbing ability significantly correlated only with MS related to body mass. The relationship between MS related to body mass and on sight ability was strong (r=0.806, p=0.016). Conclusion:EF strength and endurance appear to be key performance factors in sports climbing. Sports climbing demands a high level of EF endurance during muscle contractions of high intensity. An excessive increase of EF endurance would not necessary lead to a significant improvement in climbing ability. However, higher climbing ability demands increased EF maximal strength.Keywords: rock climbing, isometric muscle contraction, maximal strength, muscle endurance